2002
DOI: 10.1046/j.1365-2141.2002.03928.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed intrinsic fibrinolytic activity by monoclonal anti‐beta‐2 glycoprotein I autoantibodies: possible mechanism for thrombosis in patients with antiphospholipid syndrome

Abstract: Summary. b2-glycoprotein I (b2GPI) bears the epitope(s) for autoimmune anticardiolipin antibodies (aCL) frequently present in patients with antiphospholipid syndrome (APS). b2GPI is involved in coagulation and fibrinolytic systems, including inhibition of contact activation. Coagulation factor XII is an initiator of intrinsic coagulation and also of intrinsic fibrinolysis. We investigated the effect of aCL (¼ anti-b2GPI antibodies), regarding intrinsic fibrinolysis using autoimmune monoclonal anti-b2GPI antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 38 publications
1
33
0
1
Order By: Relevance
“…β2GP1 is identified as a major target antigen in patients with APS as well [37]. It has been suggested that β2GP1 and β2GP1-reactive antibodies may have direct interactions with the fibrinolytic system [38][39]. In our study, we found elevated anti-β2GP1 IgG antibodies in the plasma samples of type 1 diabetic patients.…”
Section: Discussionsupporting
confidence: 63%
“…β2GP1 is identified as a major target antigen in patients with APS as well [37]. It has been suggested that β2GP1 and β2GP1-reactive antibodies may have direct interactions with the fibrinolytic system [38][39]. In our study, we found elevated anti-β2GP1 IgG antibodies in the plasma samples of type 1 diabetic patients.…”
Section: Discussionsupporting
confidence: 63%
“…Along this line, Takeuchi et al (38) showed that the EY2C9 IgM anti-␤ 2 GPI mAb (from an APS patient) suppressed intrinsic fibrinolysis in the presence of ␤ 2 GPI, apparently by enhancing the ␤ 2 GPI-mediated weak suppression of intrinsic fibrinolysis. Similar to intrinsic coagulation, intrinsic fibrinolysis is initiated by the contact activation of coagulation factor XII (FXII).…”
Section: Discussionmentioning
confidence: 92%
“…It has also been suggested that h 2 GPI inhibits factor XII activation and that the inhibition is enhanced by anti-h 2 GPI [44]. Furthermore, suppression of intrinsic fibrinolytic activity of the euglobulin fraction from normal plasma by h 2 GPI, independent of factor XII, has been recently described and the effect is reversed by monoclonal anti-h 2 GPI antibodies in the presence of h 2 GPI [45]. Thus, h 2 GPI appears to not only interact with factors of the coagulation cascade, but also participate in the regulation of intrinsic fibrinolysis.…”
Section: Gpi and Coagulation Factorsmentioning
confidence: 93%